The role of the reserve-museums of Kazakhstan in the study and preservation of archeological monuments on the silk road (Journal of history, 2018)
The article examines the problems of historical-cultural heritage along the Great Silk Road in the context of the activities of state reserve-museums. The authors note that the creation on the ground of significant archaeological monuments of reserve-museums, within the framework of state programs, is an important tool for preserving, studying and promoting the country’s cultural heritage. The article was the first to collect and structure the material, which gives a holistic view of the role of these institutions in the conservation and exploration of archaeological complexes on the four Kazakhstan segments of the Silk Road.